PENGEMBANGAN MASJID INKLUSIF DI KOTA BANDA ACEH: MENINGKATKAN AKSESIBILITAS BAGI PENYANDANG DISABILITAS - Syarifah Hanifa Soraya (JURNAL ILMIAH GEMA PERENCANA, 2026)
This policy paper describes that Mosques as centers of religious and social activities must be inclusive and accessible for all, including people with disabilities. Accessibility in worship includes ease and comfort in using public facilities in places of worship, in this case mosques are very much needed by every individual who uses these facilities. However, many mosques in Indonesia, especially in Banda Aceh, do not meet adequate accessibility standards. So people with disabilities very rarely get the opportunity to worship comfortably and easily in places of worship, especially mosques, which causes people with this special condition to feel less confident to actualize themselves in carrying out their obligations like Muslims in general. This special condition is actually not only experienced by people who have special needs from birth, but also people who experience certain diseases or people who are elderly. This Policy Paper aims to identify obstacles and opportunities for the development of inclusive mosques, especially in the city of Banda Aceh. Using literature analysis and case studies, we recommend policies and strategies to improve mosque accessibility for people with disabilities. These recommendations include: (1) Develop adequate policies and regulations to regulate the accessibility of mosques for people with disabilities, (2) Development of inclusive and accessible mosque infrastructure for people with disabilities, and (3) Conduct training for mosque managers and administrators on the needs of people with disabilities.